PENGARUH MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP HASIL BELAJAR MAHASISWA MPI KELAS B SEMESTER IV UIN ALAUDDIN MAKASSAR - Sola, Ermi; Ismatun Amriyah Bahtiar; Musdalifa; Azwan Sudarman (Department of Islamic Education Management, 2022)
The purpose of this research is to find out the use of technology-based learning media and to find out what are the supporting and inhibiting factors for the implementation of technology-based learning. The sample is 41 students using simple random sampling technique. Data collection techniques using a questionnaire. The data processing technique uses a simple linear analysis technique. Based on the results of the study, a significance positive. Tthere is an influence between technology-based learning media on learning outcomes at UIN Alauddin Makassar Fakuktas Tarbiyah and Teacher Training Department of Islamic Education Management class B class 2020.